2007
DOI: 10.1111/j.1460-9568.2007.05943.x
|View full text |Cite
|
Sign up to set email alerts
|

Calpain‐mediated cleavage of collapsin response mediator protein(CRMP)‐2 during neurite degeneration in mice

Abstract: Axon or dendrite degeneration involves activation of the ubiquitin-proteasome system, failure to maintain neuritic ATP levels, microtubule fragmentation and a mitochondrial permeability transition that occur independently of the somal death programs. To gain further insight into the neurite degeneration mechanims we have compared two-dimensional gel electrophoresis patterns of neurite proteins from suprior cervical ganglia during degeneration caused by nerve growth factor (NGF) deprivation. We show here that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 62 publications
1
52
0
3
Order By: Relevance
“…We measured collapsin response mediator protein (CRMP)-2 to determine the mechanisms of morphological change in hippocampal neurons. CRMP-2, which is part of a family of cytoplasmic proteins in the brain, plays important roles in axon guidance (14,18,19). In this study, we found axonal degeneration and a change in CRMP-2 expression in the hippocampal neurons of vitamin E-deficient mice.…”
Section: Vitamin E Deficiency Induces Axonal Degeneration In Mouse Hisupporting
confidence: 49%
See 3 more Smart Citations
“…We measured collapsin response mediator protein (CRMP)-2 to determine the mechanisms of morphological change in hippocampal neurons. CRMP-2, which is part of a family of cytoplasmic proteins in the brain, plays important roles in axon guidance (14,18,19). In this study, we found axonal degeneration and a change in CRMP-2 expression in the hippocampal neurons of vitamin E-deficient mice.…”
Section: Vitamin E Deficiency Induces Axonal Degeneration In Mouse Hisupporting
confidence: 49%
“…Axonal degeneration was evaluated by monitoring morphological hallmarks of neurite degeneration such as beading, accumulation and fragmentation, as described previously with some modifications (14,21,22). Photomicrographs of the hippocampal CA1 region on the Bodian's stained slices were analyzed to determine axonal condition.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Later studies identified that the cleavage was by calpain (13,(22)(23)(24)(25)(26), a Ca 2ϩ -activated protease that has been heavily linked to neurotoxic signaling (27). The cleavage of CRMP2 by calpain occurs following ischemia (23), neurotrauma (26), excitotoxicity (13), and nerve growth factor deprivation-induced neurite degeneration (24).…”
Section: ؉mentioning
confidence: 99%